Socio-demographic determinants and awareness regarding hypertension among adult population in an urban slum of Mumbai, India - Yennawar, Bhakti S.; Chavan, Yuvaraj B.; Giri, Purushottam A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is a well-established risk factor for major cardiovascular diseases, thus a great challenge in modern public health. It is common, asymptomatic, readily detectable, having preventable risk factors and often lead to lethal complications if left untreated. Methods:A cross-sectional study was carried out among 133 people in the field practice area of the T. N. Medical College, Mumbai during the period of August to October 2005. A pre-designed questionnaire was used to collect necessary information such as socio-demographic profile and level of awareness regards to risk factors, and complications of hypertension as the tool of data collection. Results were analysed using Statistical Package of Social Sciences (SPSS) version -17.0. Results:In the present study, out of total 133 respondents, 60.9% were females and 39.1% were males. Awareness of modifiable risk factors for hypertension is significantly more in males than in females. As age increases awareness of non-modifiable risk factors for hypertension also increases. Socio-economic status of respondents shows significant association with awareness of complications of hypertension. Conclusions:In this study, the level of awareness regarding hypertension among study population was poor indicating a need to target the hypertension screening and awareness campaigns. Hypertension awareness can also be improved by increasing public knowledge and health education targeting general public.